Alveolar ridge augmentation in Oral and Maxillofacial Surgery: a study on current practices, patient management and innovations in Germany - Andreas Pabst; Jörg Wiegner; Matthias Schneider; Nils Weyer; Alexander Bartella; Max Heiland; Philipp Becker; Alexander-N. Zeller (International Journal of Implant Dentistry)
Abstract Introduction This study identifies current practices, patient management concepts and innovations in alveolar ridge augmentation (ARA) in Oral and Maxillofacial Surgery (OMFS) in Germany. Material and methods A survey with a dynamic online questionnaire with up to 40 questions was designed to collect general and specific data on ARA, such as case numbers, imaging, surgical techniques, (bio-)materials, and case management in OMFS. After internal and external validation, 1863 OMF surgeons within the German Association for Oral and Maxillofacial Surgery (DGMKG) were invited via email to participate. Data management was anonymized and descriptively. Results 324 OMF surgeons participated in the study (response rate 17.39%). Most participants (60.8%) work in private practices without inpatient care. 62.03% of participants insert > 200 implants, and 28.70% perform > 200 ARA annually. About 30.86% also provide implant-based prosthetic restorations. Cone-beam computed tomography (CBCT) is the imaging method most preferred by 87.74% of participants. The most common ARA techniques are external and internal sinus lift (SL) and bone block augmentation (97.31%, 90.57%, and 73.4%, respectively). Intraoral harvested autogenous bone grafts (ABG) are most commonly used for ARA (96.63%). The oblique line is the participants’ preferred donor site for ABG (93.27%). ABG and xenogeneic bone substitutes are the most frequently used graft combinations (72.73%). Platelet-rich fibrin (PRF) is used by 58.59% of participants for ARA, mostly in SL procedures (76.44%). PRF is the most common substitute used to biofunctionalize biomaterials (48.16%). Oral antibiotics are used by 86.40% pre-/intraoperatively and by 88.97% postoperatively for ARA. Most participants believe the surgical technique (94.49%) and the surgeon's experience (92.28%) are the most critical factors for ARA success. 46.32% of participants aim to perform ARA within the skeletal envelope. Conclusion The findings highlight current practices, patient management, and innovations in ARA in OMFS in Germany. They show standard practices and numerous variations in several aspects. Clinical relevance Surgical technique, experience, patient health and compliance are relevant ARA success factors. This underlies the importance of extended surgical training and careful patient selection.